Маркери ризику метаболічного синдрому у хворих із доброякісною гіперплазією передміхурової залози залежно від стадії захворювання - Кирилюк, М. Л.; Костєв, Ф. І.; Підаєв, А. В.; Шаталюк, С. С. (Clinical Endocrinology and Endocrine Surgery, 2012)
On the basis of a comprehensive survey (circumference of waist / circumference of thighs ratio, body/mass index, fasting plasma glucose, total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides, uric acid, C-reactive protein, total testosterone) of patients with BPH it was shown that all-time adverse changes of metabolic syndrome risk factors (markers) are revealing in 2nd BPH stage.